Nodular regenerative hyperplasia and liver transplantation: a systematic review - Biesterveld, Ben E.; Schroder, Paul M.; Hitchcock, Mary E.; Bolognese, Alexandra; Kim, Steven C.; Al-Adra, David P. (Frontiers in Transplantation, 2023)
Nodular regenerative hyperplasia (NRH) is a primary disease of the liver that may cause noncirrhotic portal hypertension. Common causes include autoimmune, hematologic, immune deficiency and myeloproliferative disorders. Given the limited data regarding the development of NRH in contemporary immunosuppressive protocols and the occurrence of NRH post-liver transplantation, we systematically reviewed NRH as it pertains to liver transplantation. We performed a comprehensive search for NRH and transplantation. 19 studies were identified with relevant data for NRH as an indication for liver transplant. 13 studies were identified with relevant data pertaining to NRH development after liver transplant. Pooled analysis revealed 0.9% of liver transplant recipients had NRH. 113 patients identified with NRH underwent liver transplantation. Most series report transplants done after failure of endoscopic banding and TIPS management of portal hypertension. Reported 5-year graft-and patient-survival ranged from 73-78% and 73-90%. Pooled incidence of NRH after liver transplant for all indications was 2.9% and caused complications of portal hypertension. Complications related to portal hypertension secondary to NRH are a rare indication for liver transplant. NRH can develop at any time after liver transplantation, often without an identifiable cause, which may lead to portal hypertension requiring treatment or even re-transplantation.